Isolation and Characterization of Heterotrophic Bacteria from Residential Area and Low Salinity Seawater in Purnama Village Dumai Riau Province - Mayda Susana; Feliatra '; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Heterotrophs is a bacteria that use organic carbon and inorganic nitrogen as a food source. The research was conducted from December 2016 to January 2017. The aim at this study was to isolate, determine the ability of bacteria isolates as an antibacterial to pathogenic bacteria and determine the characteristics of heterotrophic bacteria isolated from residential area and low salinity seawater based on PCR method technique 16S rDNA sequences. Isolation and identification morphology, biochemical test and antibacterial tests were analyzed in Marine Microbiology Laboratorium of Riau University. DNA and PCR analysis process was conducted in Biology Laboratorium of Riau University. The sequencing DNA process was conducted in PT. Genetika Science Indonesia, West Jakarta. The result showed that the twenty three pure isolates bacteria and only seven isolates could be sequenced. Bacterial isolates 20M2, 20M4, 20M5, 20M11, 30M6, 30M7 and 30M8 able to inhibit the growth of pathogenic bacteria. Based on the BLAST system accessed via World Wide Web, the isolated bacteria were: Bacillus toyonensis strain ACOPR1ISOXg, Bacillus subtilis strain Y37, Enterobacter cloacae strain ENC-3, Clostridium acetobulylicum strain S512, Bacillus cereus strain 4PLGES, Bacillus cereus strain ML267 and Bacillus thuringensis strain C17.Keywords: heterotrophic bacteria, isolation, characterization, 16S rDNA